Sleep and learning in school children (Research, Society and Development, 2020)
Objectives: To discuss physiological factors that affect learning in school children and the harmful effects of major sleep disturbances on that age. Methodology: Articles were analysed between 2020 and 2015 in LILACS, PUBMED, SciELO and MEDLINE databases with the keywords: Sleep and Child; Sleep and Learning; GH and Learning; Memory and Learning; Blood Flow and Learning; Oxygenation and Learning; Immunity and Cognition. Additionally, we also referred to the books "Sleep and Sleep Medicine" and "Insomnia from Diagnosis to Treatment". Results and discussion: We found evidence in the literature that sleep influences brain plasticity, spatial learning, motor training, long-term memory, Growth Hormone (GH) release, synapses remodelling and acts on the Hypothalamic-pituitary-adrenal (HPA) axis. Furthermore, clinical and practical findings also show that immunity is affected and children with sleep problems present significant disturbances in learning. Conclusion: The relationships between sleep reduction/ sleep disorders and daytime /nocturnal brain function, influence learning of school children.